Dakwah Sufistik Sebagai Penangkal Radikalisme - Yudi, Diah Titi Nawang; Halwati, Umi (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2024)
Islamic radicalism develops the principle that Islamic ideology must be upheld in state life. In its application, radical understanding tends to use violent means and also acts of terror. This is certainly compared to the islamic religious concept of rahmatan lil al-'alamin and the concept of proselytizing taught by the Prophet. In fact, the purpose of proselytizing is not in how much territory or how many people embrace Isam, but rather in the effort to sanctify the souls of its adherents. So that the concept of jihad, which has been echoed by radicalism, has a shift in meaning from its true meaning. This research uses a literature approach so that the data obtained are sourced from various books, articles and also notes from previous research. After the analysis, the results were obtained that the development of radicalism was based on the background of the fundamentalist understanding that developed in society. One method of proselytizing that can be used to suppress radicalism is sufistic proselytizing. In sufistic proselytizing there is the concept of mahabbah or love, where love here is not seen superficially rather than just the relationship with the god. However, love and establishing a good relationship with fellow human beings are also included in the path to reaching divine love.